Scalability of Parallel Batch Pattern Neural Network Training Algorithm - Turchenko, V. (Інститут проблем штучного інтелекту МОН України та НАН України, 2009)
The development of parallel batch pattern back propagation training algorithm of multilayer perceptron and its scalability research on general-purpose parallel computer are presented in this paper. The model of multilayer perceptron and batch pattern training algorithm are theoretically described. The algorithmic description of the parallel batch pattern training method is presented. The scalability research of the developed parallel algorithm is fulfilled at progressive increasing the dimension of the parallelized problem on general-purpose parallel computer NEC TX-7.